Sex‐specific clinical outcomes after cardiac resynchronization therapy in left bundle branch block‐associated idiopathic nonischemic cardiomyopathy: A NEOLITH II substudy. Issue 4 (27th March 2019) - Wang, Norman C.; Mezu‐Chukwu, Ure; Adelstein, Evan C.; Althouse, Andrew D.; Sharbaugh, Michael S.; Jain, Sandeep K.; Shalaby, Alaa A.; Voigt, Andrew H.; Saba, Samir
Abstract: Background: Sex differences in clinical outcomes for left bundle branch block (LBBB)‐associated idiopathic nonischemic cardiomyopathy (NICM) after cardiac resynchronization therapy (CRT) are not well described. Methods: A retrospective cohort study at an academic medical center included subjects with LBBB‐associated idiopathic NICM who received CRT. Cox regression analyses estimated the hazard ratios (HRs) between sex and clinical outcomes. Results: In 123 total subjects (mean age 62 years, mean initial left ventricular ejection fraction 22.8%, 76% New York Heart Association class III, and 98% CRT‐defibrillators), 55 (45%) were men and 68 (55%) were women. The median follow‐up time after CRT was 72.4 months. Similar risk for adverse clinical events (heart failure hospitalization, appropriate implantable cardioverter‐defibrillator shock, appropriate antitachycardia pacing therapy, ventricular assist device implantation, heart transplantation, and death) was observed between men and women (HR, 1.20; 95% confidence interval [CI] 0.57–2.51; p = 0.63). This persisted in multivariable analyses. Men and women had similar risk for all‐cause mortality in univariable analysis, but men had higher risk in the final multivariable model that adjusted for age at diagnosis, QRS duration, and left ventricular end‐diastolic dimension index (HR, 4.55; 95% CI, 1.26–16.39; p = 0.02). The estimated 5‐year mortality was 9.5% for men and 6.9% for women. Conclusions: In LBBB‐associated idiopathic NICM, men have higher risk for all‐cause mortality after CRT when compared to women.